2015
DOI: 10.1590/s1806-37132015000004531
|View full text |Cite
|
Sign up to set email alerts
|

Identifying activating mutations in the EGFR gene: prognostic and therapeutic implications in non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Promising new therapies have recently emerged from the development of molecular targeted drugs; particularly promising are those blocking the signal transduction machinery of cancer cells. One of the most widely studied cell signaling pathways is that of EGFR, which leads to uncontrolled cell proliferation, increased cell angiogenesis, and greater cell invasiveness. Activating mutations in the EGFR gene (deletions in exon 19 and mutation L858… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 72 publications
1
16
0
5
Order By: Relevance
“…Approximately 13% of the NSCLC patients have EGFR mutations such as L858R and these patients initially respond to the TKI such as erlotinib or gefitinib [25, 32]. Subsequently NSCLC patients become resistant to erlotinib or gefitinib due to secondary EGFR mutations such as T790M [24]. It is important to increase the sensitivity of TKI in NSCLC patients with wild type EGFR or secondary T790M mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 13% of the NSCLC patients have EGFR mutations such as L858R and these patients initially respond to the TKI such as erlotinib or gefitinib [25, 32]. Subsequently NSCLC patients become resistant to erlotinib or gefitinib due to secondary EGFR mutations such as T790M [24]. It is important to increase the sensitivity of TKI in NSCLC patients with wild type EGFR or secondary T790M mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cancer invasiveness is stimulated by numerous mechanisms, including activating EGFR mutations [33]. Furthermore, a recent meta-analysis by Wang and Wang [34] exploring the correlation of EGFR status between primary tumors and metastases revealed that EGFR mutations should occur before metastasis, suggesting that EGFR mutations play a role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…They postulated that the differences might be explained by different ethnic makeup of these countries. Argentina, for example, has a predominantly white population, with lower reported rates than Peru, where there have traditionally been higher rates of Asian migration .…”
Section: Introductionmentioning
confidence: 99%